Insights into the Substrate Promiscuity of Novel Hydroxysteroid Dehydrogenases. Issue 12 (28th April 2020) - Bertuletti, Susanna; Ferrandi, Erica Elisa; Marzorati, Stefano; Vanoni, Marta; Riva, Sergio; Monti, Daniela
Abstract: Hydroxysteroid dehydrogenases (HSDHs) are valuable biocatalysts for the regio‐ and stereoselective modification of steroids, bile acids and other steroid derivatives. In this work, we investigated the substrate promiscuity of this highly selective class of enzymes. In order to reach this goal, a preliminary search of HSDH homologues in in‐house or public available (meta)genomes was carried out. Eight novel NAD(H)‐dependent HSDHs, showing either 7α‐, 7β‐, or 12α‐HSDH activity, and including, for the first time, enzymes from extremophilic microorganisms, were identified, recombinantly produced, and characterized. Among the novel HSDHs, four highly active (up to 92 U mg −1 ) NAD(H)‐dependent 7β‐HSDHs showing negligible similarity towards previously described 7β‐HSDHs, were discovered. These enzymes, along with previously characterized HSDHs, were tested as biocatalysts for the stereoselective reduction of a panel of substrates including two α‐ketoesters of pharmaceutical interest and selected ketones that partially resemble the structural features of steroids. All the reactions were coupled with a suitable cofactor regeneration system. Regarding the α‐ketoesters, nearly all of the tested HSDHs showed a good activity toward the selected substrates, yielding the reduced α‐hydroxyester with up to 99% conversions and enantiomeric excesses. On the other hand, only the 7β‐HSDHs from Collinsella aerofaciens and Clostridium absonum showed appreciable activity toward more complex ketones, i. e., (±)‐trans‐1‐decalone, but with interesting as well as different selectivity. Abstract :